O viver e o produzir no contexto da educação do campo: o caso da Escola Estadual de Ensino Fundamental Dirceu Moreira, Pelotas - RS - Barros, Lânderson Antória (2014)
The Brazilian agrarian space, from the second half of the twentieth century, has undergone numerous transformations through agricultural modernization process and the "Green Revolution . The new goals set for the Brazilian countryside interfered directly in the social relations of the farmer, as concurrently to the modernization process, an increase in the dependence of producers in relation to external factors, and other significant economic, social, cultural and environmental impacts. From this context means be extremely important to establish a new education project in schools located in rural areas, as this has a big role in these spaces. The design built between students, children of farmers, on the agrarian space more specifically family farming can be a determining factor in keeping these subjects in the field valuing their culture, thus enabling the social reproduction of these actors, This work has the theme guiding the perspective of rural students about their place to live and produce, highlighting and understanding the importance of field school in these aspects. The object where the study was the School EPS Dirceu Moreira, located on the 6th Pelotas district known as Santa Silvana. Thus, we understand during the interviews how students perceive the appropriation of nature from their relations with the place to live and produce. We can identify several problems in school, including the school's precariousness and the lack of new development perspectives to the location.